Civil war impacts on youth business groups in Tigray: A preanalysis plan and documentation for ethical approval by institutional review board at NMBU - Stein Terje Holden; Mesfin Tilahun; Dag Einar Sommervoll; Erlend Dancke Sandorf (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2023)
This is a revised plan for the finalization of the "Youth Groups for Sustainable Development: Lessons from the Ethiopian Model" (Researcher project under NORGLOBAL2, funded by the Research Council of Norway). The project started in 2019 and was planned to last for four years. A civil war broke out in the study areas in November 2020 and made it impossible to continue the project according to the initial plan. A lot of survey and experimental data had already been collected by this time and the project was in the process of implementing a number of Randomized Control Trials (RCTs) on business group training, leadership, and women's empowerment. These RCTs were planned implemented and analyzed in collaboration with a number of international partners. We were unfortunately unable to do this. The civil war lasted for two years and a substantial share of the project funds were locked into local banks and the local collaborating university (Mekelle University) that were closed down during the civil war. We asked for an extension of the project to the end of 2023 and was granted this by the Research Council of Norway - to enable us to do a final assessment what has happened to the youth groups, their members, and families during the civil war and to assess the youth (business) groups' role in the recreation of the members' livelihoods after the civil war. We were informed on June 15th, 2023, that the project funds that have been locked in the bank in Mekelle since the civil war started can be accessed through Mekelle University for the continuation of the project fieldwork. We submitted this plan and application for ethical approval at NMBU on June 16th, 2023. Approval was received on August 3rd, 2023. Some minor revisions were implemented based on the review and further preparation of baseline data from 2019. Training of the field team and programming of final survey instruments with translation into the local language Tigrinya started immediately. The training and pilot testing of the instruments were completed by August 19th, 2023. The actual fieldwork started on August 22nd after some final editing of the experiments. This report thus presents the final instruments.
hdl:11250/3085805
Keywords: 330; Civil war; business groups; impact assessment; group performance; assets; trust; social and economic preferences; welfare outcomes